Estilos de educación familiar y logros de aprendizaje en el área de comunicación en niños de la Institución Pública Inicial N° 493 Mi dulce hogar comunidad de San Jorge río Marañon, Nauta 2021 - Villanueva Diaz, Blanca Irma (2024)
The study starts from the question: How is the relationship between family education styles and learning achievements in the area of communication in children of the Initial Public Institution No. 493 Mi Dulce Hogar in the community of San Jorge? to give a Proven response is proposed as an objective to relate the styles of family education and the achievement of learning in the mentioned area and children. The study design is field, cross-sectional, bivariate, non-experimental, with the type of relational research. The survey and observation technique were applied to collect data through a questionnaire and observation guide, instruments validated in advance by experts, to a sample of 21 children. Conclusion: That when carrying out the categorical ordinal relationship between family education styles and learning achievement in the area of communication with Kendall's Tau-B statistical test, it is observed that there is only a significant relationship with the democratic style, which is corroborates the relationship hypothesis raised in the present investigation.